(untitled) (International Association of Biologicals and Computational Digest, 2023)
Grangea maderaspatana (L.) Poir., also known as Madras Carpet, is a medicinal flowering plant in the Asteraceae family. This is a common weed that grows in sandy soils and waste areas. This plant has produced a wide range of phytochemical substances. It has been used for thousands of years in traditional Ayurveda Indian medicine to treat a number of diseases. This plant has oestrogenicity, antifertility, analgesic, anti-inflammatory, antiarthritic, cytotoxic, antioxidant, hepatoprotective, diuretic, and antibacterial effects have all been studied. The leaves have stomachic, a sedative, carminative, emmenagogue, and antiflatulent properties. The review covers biological activity phytochemicals derived from these plants in detail.